2015
DOI: 10.1149/2.0441602jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Transport Phenomena in Hybrid Pseudocapacitors under Galvanostatic Cycling

Abstract: This study aims to provide insights into the electrochemical transport and interfacial phenomena in hybrid pseudocapacitors under galvanostatic cycling. Pseudocapacitors are promising electrical energy storage devices for applications requiring large power density. They also involve complex, coupled, and multiscale physical phenomena that are difficult to probe experimentally. The present study performed detailed numerical simulations for a hybrid pseudocapacitor with planar electrodes and binary, asymmetric e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 75 publications
3
24
0
Order By: Relevance
“…In short, they were noted differences when MWCNTs with different oxygencontaining groups were electrochemically characterised using a different cationic radius of group one sulfate electrolyte systems. This corroborates with earlier studies that concluded that electrolyte transport characteristics change with local electric fields [56]. An ideal EDLC character is one that is classically associated with fast reversible reactions, that is, rectangular CV.…”
Section: Potassium Sulfate Electrolytesupporting
confidence: 91%
“…In short, they were noted differences when MWCNTs with different oxygencontaining groups were electrochemically characterised using a different cationic radius of group one sulfate electrolyte systems. This corroborates with earlier studies that concluded that electrolyte transport characteristics change with local electric fields [56]. An ideal EDLC character is one that is classically associated with fast reversible reactions, that is, rectangular CV.…”
Section: Potassium Sulfate Electrolytesupporting
confidence: 91%
“…Recently, we presented a first-principles continuum model for the electrochemical interfacial and transport phenomena in hybrid pseudocapacitors under galvanostatic cycling [25].…”
Section: Interfacial and Transport Phenomena In Pseudocapacitorsmentioning
confidence: 99%
“…Our previous simulation studies that were used to characterize electric double layer capacitors with asymmetric electrolytes or hybrid pseudocapacitors were based on two-electrode configurations. [8][9][10][11][12] While these studies are extremely useful for providing insight on device characteristics, they are not designed to contribute detailed understanding of the electrode material, which is frequently the focus of experimental studies on pseudocapacitor. Indeed, the current in two-electrode hybrid pseudocapacitors is controlled by the carbon electrode whereas the current in three-electrode measurements is only limited by redox reactions and interfacial and transport phenomena through or near the pseudocapacitive electrode.…”
Section: Introductionmentioning
confidence: 99%